Dziecko z zaburzeniami zachowania – trudności i przeszkody w postępowaniu terapeutycznym - Cygan, Barbara; Kurowska, Barbara (Kultura-Społeczeństwo-Edukacja, 2023)
The article discusses the problem of functioning of a child diagnosed with behavioral disorders. In particular, the focus is on the difficulties and obstacles of therapeutic procedures and the factors that cause them. The symptoms and causes of behavioral disorders were indicated, including environmental factors that may intensify the observed difficult behaviors, which are a component of behavioral disorders.